Enhanced Written vs. Verbal Recall Accuracy Associated With Greater Prefrontal Activation: A Near-Infrared Spectroscopy Study - Zhang, Jianan; Wang, Ya; Zhang, Yu; Li, Brian; Zhang, Yi (Frontiers in Behavioral Neuroscience, 2021)
BACKGROUND Memory efficiency is influenced by the modalities of acquisition and retrieval. The recall accuracy of read or voiced material differs depending on whether the recall is given verbally or in writing. The medial prefrontal cortex (mPFC) is critical for both attentional allocation and short-term memory, suggesting that different short-term memory recall modalities are associated with distinct mPFC processes and activation patterns. METHODS Near-infrared spectroscopy (NIRS) was used to monitor mPFC oxygenation parameters of 30 healthy subjects during acquisition and recall tasks as a measure of neural activity. Oxygenation parameters and recall accuracy were compared between oral and written answers and the potential correlations were analyzed. RESULTS Written responses were more accurate than verbal responses to the same questions and evoked greater changes in mPFC oxyhemoglobin (oxyHb) and total Hb (total-Hb). Furthermore, there were significant positive correlations between recall accuracy and both [oxyHb] and [total-Hb] in the mPFC. CONCLUSION Memory accuracy of written material is greater when responses are also written rather than verbal. In both cases, recall accuracy was correlated with the degree of mPFC activity. This NIRS-based learning and memory paradigm may be useful for monitoring training efficacy, such as in patients with cognitive impairment.